Studies on social defeat : biomarkers of stress-induced states and influences on individual reactivity to social stress - Vasconcelos, Mailton França de (2014)
The rat social defeat is ethologically relevant and useful paradigm to understand stress effects. A systematic review of biomarkers induced by social defeat protocol presented in scientific publications in electronic databases in the period of 2002 to 2013 was carried out. Classical and more recently described biomarkers relevant for stress-induced states were identified in the searches. These results were discussed with social defeat protocol relevancy. An experimental study of rat social defeat and immunologic and behavioral stress-induced consequences was executed. The hypothesis of the experimental study are based on evidence that social stress influences immunological responses, also individual variability plays an important influence on effects of stress exposure. In order to evaluate these hypotheses an intermittent social defeat protocol was conducted. Social stress did not affect weight gain and peripheral immunological measures. In the first stress encounter it was possible to characterize individuals in two categories according to their behavioral strategy. These results supported theoretical inferences of social stress equalizing effects on individual reactivity to environmental stimuli.